A Framework For Dynamic Updating In Component-Based Software Systems. - Alhazbi, Saleh; Jantan, Aman (2007)
This paper presents DPICS framework for composing component-based software system that can be modified at runtime. It is based on message pattern interaction between system’s components, which facilitates adding, removing, or replacing a component while the whole system is running.